Secessionist Movements and the National Question in Nigeria: A Revisit to the Quest for Political Restructuring - Awofeso, Olu (IJRDO - Journal of Social Science and Humanities Research, 2017)
Nigeria is currently facing several challenges arising from unresolved national question revolving around sensitive national issues like group marginalization, revenue allocation, politicalisation of religion, ethnic militancy, terrorism, corruption, etc. One major manifestation of some of these unresolved problems is the emergence of groups demanding for self-determination and political independence as witnessed among the Indigenous People of Biafra (IPOB) in South-East, the NigerDelta Avengers (NDA) in South-South and several other groups in different parts of the country. Although, threats of secession and secessionist movements are not entirely new to Nigerian politics, the dimension they have assumed today are not unconnected to the national question. The paper against this background examines the relationship between some of these unresolved questions and the on-going agitation for self-determination by some groups within the Nigerian state. Apart from identifying these activities as collective threat to national unity, the paper also analyses the prospect of restructuring Nigeria politically as a remedy to these challenges. The paper concludes by proffering suggestions for the unity of the country.